2023
DOI: 10.1039/d3sc00102d
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stable redox states and tunable ground states via the marriage of viologens and Chichibabin's hydrocarbon

Abstract: Herein, we report the isolation of bis-BN-based species 1 and 2 with multiple stable redox states. Their ground states are tunable with 1 as a closed-shell singlet and 2 as an open-shell singlet with a small singlet-triplet gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…AP 1 displays well-resolved 1 H NMR signals at room temperature, indicating the dominating closed-shell structure of the πconjugated core in AP 1 C. However, obvious broadening was observed in the NMR spectra of both AP 1 * and AP 2 * at 298 K, which is due to the existence of the dominating radical cations and probably minor fraction of dications. [15] Similar results of NMR were found in AP 2 and AP 2 * (Figure S10). The presence of unpaired electrons results in broadened NMR resonances owing to increased relaxation rates.…”
Section: Polymer Synthesis and Characterizationsupporting
confidence: 78%
See 1 more Smart Citation
“…AP 1 displays well-resolved 1 H NMR signals at room temperature, indicating the dominating closed-shell structure of the πconjugated core in AP 1 C. However, obvious broadening was observed in the NMR spectra of both AP 1 * and AP 2 * at 298 K, which is due to the existence of the dominating radical cations and probably minor fraction of dications. [15] Similar results of NMR were found in AP 2 and AP 2 * (Figure S10). The presence of unpaired electrons results in broadened NMR resonances owing to increased relaxation rates.…”
Section: Polymer Synthesis and Characterizationsupporting
confidence: 78%
“…The VT‐EPR spectra of the four polymers ( AP 1 , AP 1 *, AP 2, AP 2 * ) in solid states are shown in Figures 4c–f. Upon cooling, the signal intensities gradually decreased, which is typical for open‐shell singlet diradicaloids [2d,15,20] . These EPR results, combined with the thermo‐induced behaviours (see below), imply the presence of singlet ground state for the anthraquinone radicals in these polymers at a low temperature, leading to antiferromagnetic behavior and reduced EPR signal with the decrease of the temperature [21] .…”
Section: Resultsmentioning
confidence: 80%
“…In the UV‐vis absorption spectrum, compound 1 displays a maximum absorption band at 569 nm (Figure 2), which is greatly bathochromically shifted in comparison with those of VI (398 nm) and VII (411 nm) and is comparable to that (527 nm) of the 3,3’,5,5’‐tetramethyl substituted bis‐BN‐based analogue VIII of Chichibabin's hydrocarbon, [ 12 ] suggesting the diradical nature of 1 . And compound 2 exhibits two further red‐shifted absorption bands at 648 and 613 nm (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, by replacement of both terminal C=C bonds in Thiele's and Chichibabin's hydrocarbons with the isoelectronic B=N bonds, we isolated bis‐BN‐based analogues of Thiele's ( VI ) and Chichibabin's ( VII ) hydrocarbons possessing the bulky 1,3,2‐diazaborolyl ligands. [ 11‐12 ] However, both are closed‐shell singlets in their ground states. We envision that the elongation of the central linkers and modification of the terminal groups could have an effect on their ground states.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Conjugated p-systems that possess biradical character [1][2][3][4][5][6] hold tremendous promise as novel architectures for molecular and molecule-based materials due to their remarkable magnetic, optical, and electronic properties. As a result, these p-conjugated biradical systems are expected to contribute to the organic semiconductor, [7][8][9] singlet ssion, 1 break junction, 10 spintronics, 11,12 non-linear optical, and exchange-coupled electron spin qubit [13][14][15][16][17] knowledge base and function as models for understanding the effects of dipolar coupling and molecular vibrations on spin relaxation. 18 It has recently been shown that the introduction of biradicaloid character into the bridge fragment in break-junction molecular conductance studies dramatically modies the distance dependence of the conductance, 10,19,20 leading to reversed conductance decay behavior where an increase in conductance with increasing molecular wire length is observed.…”
Section: Introductionmentioning
confidence: 99%